Procalcitonin in children admitted to hospital with community acquired pneumonia. Issue 4 (1st April 2001) - Moulin, F; Raymond, J; Lorrot, M; Marc, E; Coste, J; Iniguez, J-L; Kalifa, G; Bohuon, C; Gendrel, D
Abstract : AIMS: To assess the sensitivity, specificity, and predictive value of procalcitonin (PCT) in differentiating bacterial and viral causes of pneumonia. METHODS: A total of 72 children with community acquired pneumonia were studied. Ten had positive blood culture for Streptococcus pneumoniae and 15 had bacterial pneumonia according to sputum analysis ( S pneumoniae in 15, Haemophilus influenzae b in one). Ten patients had Mycoplasma pneumoniae infection and 37 were infected with viruses, eight of whom had viral infection plus bacterial coinfection. PCT concentration was compared to C reactive protein (CRP) concentration and leucocyte count, and, if samples were available, interleukin 6 (IL-6) concentration. RESULTS: PCT concentration was greater than 2 μg/l in all 10 patients with blood culture positive for S pneumoniae ; in eight of these, CRP concentration was above 60 mg/l. PCT concentration was greater than 1 μg/l in 86% of patients with bacterial infection (including Mycoplasma and bacterial superinfection of viral pneumonia). A CRP concentration of 20 mg/l had a similar sensitivity but a much lower specificity than PCT (40% v 86%) for discriminating between bacterial and viral causes of pneumonia. PCT concentration was significantly higher in cases of bacterial pneumonia with positive blood culture whereas CRP concentration was not. Specificity and sensitivity were lower for leucocyte count and IL-6 concentration. CONCLUSIONS: PCT concentration, with a threshold of 1 μg/l is more sensitive and specific and has greater positive and negative predictive values than CRP, IL-6, or white blood cell count for differentiating bacterial and viral causes of community pneumonia in untreated children admitted to hospital as emergency cases.